Effects of plyometric training on sports performance - Booth, M. A.; Orr, R. (Strength and Conditioning Journal, 2016)
Plyometric training is a series of explosive body weight resistance exercises using the stretch-shortening cycle of the muscle fiber to enhance physical capacities such as speed, strength, and power. These physiologic measures translate to improved performance in many sports, including court-based sports, field sports, and water sports. Performance enhancements resulting from plyometric training, include improved sprint times over distances ranging from 5 to 40 m, maximal muscle strength and power, and injury prevention measures such as improved landing mechanics, decreased ground reaction forces, and improved hamstring to quadriceps ratios. The optimal dose for athletic enhancements has not been consistently identified.